The Role of Public Relations in Shaping Political Communication in Nigeria: A Literature Review - Heavens Ugochukwu Obasi (Darul Yasin Al Sys, 2026)
Public relations (PR) plays an increasingly important role in shaping political communication within Nigeria’s ethnically diverse society and complex media environment. This literature review aims to examine the strategies, influence, and challenges of PR in Nigerian political communication, with particular attention to political campaigns, crisis communication, digital media, and public perception. The review draws on relevant literature and illustrative cases, including the 2023 general elections and the EndSARS movement, while applying the two-way symmetrical model and agenda-setting theory to interpret PR practices within Nigeria’s political discourse. The findings indicate that PR strategies can strengthen constituent engagement, shape public opinion, mobilize grassroots participation, influence voter behavior, and support political actors in managing crises. Digital media has further expanded the reach and immediacy of political communication, but it has also intensified misinformation, political polarization, ethical concerns, and declining public trust. The reviewed cases demonstrate that PR can facilitate democratic participation and collective action when applied transparently and responsibly, yet manipulative or misleading communication may undermine electoral integrity and democratic legitimacy. The study concludes that effective political PR in Nigeria requires stronger media relations, improved public media literacy, transparent crisis communication, and consistent adherence to professional ethical standards. These findings contribute to understanding the intersection of public relations and political communication and offer practical implications for PR practitioners, political actors, scholars, media institutions, and policymakers seeking to strengthen public trust and democratic communication in Nigeria.